Concentrations of ceftriaxone (1,000 milligrams intravenously) in abdominal tissues during open prostatectomy. - Martin, C (1996)
Ceftriaxone concentrations in abdominal tissues were evaluated at different stages of open prostatectomy. Ceftriaxone was administered as antibiotic prophylaxis, and 15 consecutive patients were given a single dose of ceftriaxone (1,000 mg intravenously in 1 min) 30 min before surgery. Ceftriaxone concentrations in tissue were determined at three stages of the surgical procedure; upon the opening of the abdominal cavity, during the prostatectomy, and upon the closure of the abdominal cavity. Samples of the following tissues or sample were assayed: epiploic and abdominal-wall fat; Retzius' space, bladder, and prostate tissue; and urine. During the different stages of the surgical procedure, for all patients, and in the different tested tissues, ceftriaxone concentrations greater than or equal to the cutoff point (4 micrograms/g of tissue) were measured. The highest concentrations were obtained in the bladder (43 +/- 18 micrograms/g) and in the prostate (35 +/- 18 micrograms/g). In fatty tissues, concentrations were between 13 +/- 5 and 22 +/- 8 micrograms/g. All patients (15 of 15) had ceftriaxone levels in tissue greater than the MICs for the potential pathogens (Staphylococcus aureus, Escherichia coli, Klebsiella pneumoniae, and Proteus mirabilis). In conclusion, during open prostatectomy and after the use of a single dose of ceftriaxone (1,000 mg), high antibiotic levels were obtained throughout the surgical procedure in the tissues potentially involved in postoperative infection.